Pattern of Paediatric Brain Tumours Evaluated in BSMMU, Dhaka, Bangladesh - Jahan, Fauzia; Kamal, Mohammed; Sultana, Shamsunnahar (Bangladesh Journal of Child Health, 2014)
Background: In children Central Nervous System (CNS) is the second most common site for primary tumours superseded only by leukaemias. Paediatric brain tumours differ from adult one by their type, location and outcome. Objectives: To study the frequency and histomorphological spectrum of CNS tumours in Children and to correlate with age, sex and distribution of tumours. Methodology: This study was carried out at the Department of Pathology, Bangabandhu Shiekh Mujib Medical University (BSMMU) Dhaka during the period of July 2006 to June 2007. Samples from all Paediatric age and both sexes were included in this study. Results: We studied 55 cases of Paediatric CNS tumours. The patients age ranged between 2 months to 15 years. The mean age at diagnosis was 10.12±4.18 years. Regarding location 59% was infratentorial and 41% were supratentorial. Most common tumour was medulloblastoma (23%). Twenty Seven (27%) of the tumours were high grade. DOI: http://dx.doi.org/10.3329/bjch.v37i3.18619 Bangladesh J Child Health 2013; Vol.37(3): 154-157